Development of a new coating raw material based on a mixture of epoxidized palm olein and diglycidyl ether of bisphenol a / Reihan Mohd Taharim - Mohd Taharim, Reihan (2014)
Epoxy coatings are highly in demand due to their excellent corrosion protective properties. Currently, raw materials for epoxy coatings mainly originate from diglycidyl ether of bisphenol A (DGEBA), a compound derived from petrochemicals. However, health concerns associated with bisphenol A, combined with the limited supply of petroleum are driving researchers to look for alternative raw materials. Plant oils are considered as potential alternative resources to generate more environmentally-friendly coating formulations. This study aims to investigate the possibility of developing a new raw material for coating using a mixture of epoxidized palm olein (EPO) and DGEBA. and subsequently evaluate the resulting coating filnr s properties and performance. The main study was done in four stages. In the first stage, coatings containing 0-30 wt. % EPO were formulated and applied on mild steel plates. The coating was then tested for adhesion, hardness, chemical resistance, water resistance and solvent resistance. The third and final stages consisted of EIS study and performance tests, respectively. The EIS study shows that the corrosion protection from EPO is comparable to that of a conventional epoxy coating. Natural weathering test was carried out for 90 days while a cyclic salt fog/UV exposure test took place for 30 days. EP030 did not show any sign of rusting or blistering upon exposure to both weathering conditions. Weathering study indicated that EPO imparted to the EPO/epoxy coating a higher tendency to discolor upon weathering in comparison on conventional epoxy coatings. Nonetheless, EIS response and weathering test results suggested that EP030 performed as well as conventional epoxy coatings in protecting metallic substrates from corrosion.